Health and Employment after Fifty (HEAF): a new prospective cohort study. (December 2015) - Palmer, Keith; Walker-Bone, Karen; Harris, E.; Linaker, Cathy; D'Angelo, Stefania; Sayer, Avan; Gale, Catharine; Evandrou, Maria; van Staa, Tjeerd; Cooper, Cyrus; Coggon, David
Abstract Background Demographic trends in developed countries have prompted governmental policies aimed at extending working lives. However, working beyond the traditional retirement age may not be feasible for those with major health problems of ageing, and depending on occupational and personal circumstances, might be either good or bad for health. To address these uncertainties, we have initiated a new longitudinal study. Methods/design We recruited some 8000 adults aged 50–64 years from 24 British general practices contributing to the Clinical Practice Research Datalink (CPRD). Participants have completed questionnaires about their work and home circumstances at baseline, and will do so regularly over follow-up, initially for a 5-year period. With their permission, we will access their primary care health records via the CPRD. The inter-relation of changes in employment (with reasons) and changes in health (e.g., major new illnesses, new treatments, mortality) will be examined. Discussion CPRD linkage allows cost-effective frequent capture of detailed objective health data with which to examine the impact of health on work at older ages and of work on health. Findings will inform government policy and also the design of work for older people and the measures needed to support employment in later life, especially for those with health limitations.